Use of surgical techniques in periodontics: Literature review (Research, Society and Development, 2021)
Periodontal surgery is an important part of periodontal treatment and must be taken into account when conventional therapy does not eliminate the periodontal problem. It is also indicated in some aesthetic cases or cases in which it is necessary to improve access to a certain area in order to carry out the correct treatment plan. The aim of the present study is to present the main indications for periodontal surgical techniques and to detail the procedures presented in the literature. This is a literature review, based on books and scientific articles present in PubMed, Scielo and Google Scholar. It is important to note that non-surgical periodontal therapy precedes surgical periodontal treatment. The association between mucogingival surgery and grafts has shown a positive result in the treatment of gingival recessions, as well as regenerative surgery with the use of biomaterials has shown efficacy in the treatment of periodontal bone defects. Periodontal surgery can be used as an important tool in the treatment of various periodontal problems.